Severe Acute Respiratory Syndrome Coronavirus-2 Seropositivity in South-Central Uganda, During 2019 - 2021 - Ssuuna, Charles; Galiwango, Ronald Moses; Kankaka, Edward Nelson; Kagaayi, Joseph; Ndyanabo, Anthony; Kigozi, Godfrey; Nakigozi, Gertrude; Lutalo, Tom; Ssekubugu, Robert; Wasswa, John Bosco; Mayinja, Anthony; Nakibuuka, Martina Cathy; et al. (Research Square, 2021)
Globally, key subpopulations such as healthcare workers (HCWs) have a higher risk of contracting SARS-CoV-2. In Uganda, limited access to personal protective equipment amidst lack of clarity on the extent and pattern of the community disease burden may exacerbate this situation. We assessed SARS-CoV-2 antibody seroprevalence among high-risk sub-populations in South-central Uganda, including HCWs, persons within the general population previously reporting experiencing key COVID-19 like symptoms (fever, cough, loss of taste and smell) and archived plasma specimens collected between October 2019 – 18th March 2020, prior to confirmation of COVID-19 in Uganda.
Keywords: SARS-CoV-2 seroprevalence; Healthcare workers; COVID-19; South-central Uganda